2009
DOI: 10.1111/j.1365-2036.2009.04069.x
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analysis: clinicopathological and prognostic significance of cyclooxygenase‐2 expression on oesophageal squamous cell carinoma

Abstract: SUMMARY BackgroundCyclooxygenase-2 (COX-2) is involved in oesophageal carcinogenesis, but the clinical and prognostic significance of COX-2 expression in oesophageal squamous cell carcinoma (ESCC) remains controversial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…Our result was consistent with previous meta-analysis conducted by Li et al45 In previous meta-analysis, they only focus on ESCC and their literature search time was closed on December 2008. Our meta-analysis included more studies and larger sample size to comprehensively evaluate the prognostic and clinicopathological significance of COX-2 expression in patients with EC (including ESCC and EADC).…”
Section: Discussionsupporting
confidence: 92%
“…Our result was consistent with previous meta-analysis conducted by Li et al45 In previous meta-analysis, they only focus on ESCC and their literature search time was closed on December 2008. Our meta-analysis included more studies and larger sample size to comprehensively evaluate the prognostic and clinicopathological significance of COX-2 expression in patients with EC (including ESCC and EADC).…”
Section: Discussionsupporting
confidence: 92%
“…There were several meta-analyses studying the prognostic value of COX-2 in other cancer types, such as lung cancer and esophageal cancer [29], [30]. The results suggest COX-2 could be of importance in early-stage NSCLC, and its impact might be lost at later steps because of the potential interaction with many factors [29].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that PLA2G2A and COX-2 gene single nucleotide polymorphisms (SNPs) (Liu et al, 2014). However, the relationship between PLA2G2A and COX-2 protein expression and ESCC clinical features remains controversial in the literature (Li et al, 2009;Ren et al, 2013). Moreover, a correlation between the co-expression of PLA2G2A and COX-2 in ESCC has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%